Sebuah Penerapan Achievement Motivation Training (AMT) untuk Meningkatkan Kepercayaan Diri Pada Peserta Didik Jurusan Teknik Komputer dan Jaringan Rumah Gemilang Indonesia, Depok: Indonesia - Pratiwi, Aisyah; Anisah, Siti; Zulkarnain, Leonardo (Jurnal Abdimas Madani dan Lestari (JAMALI), 2023)
Many factors influence students' motivation to achieve success during the academic completion process they are pursuing. One thing that is of concern is the level of their self-confidence. This is a problem experienced by students at Rumah Gemilang Indonesia. Achievement Motivation Training (AMT) is an intervention that is usually implemented to increase achievement and self-confidence. Therefore, this research is intended to examine the influence of Achievement Motivation Training (AMT) in developing the self-confidence of students majoring in Computer and Network Engineering at the Rumah Gemilang Indonesia Foundation. It is hoped that the implications of this research will be an alternative solution for improving student achievement. This research utilized a questionnaire method consisting of a Pre-Test and Post-Test on 11 students majoring in Computer and Network Engineering at RGI with the application of AMT through workshops and discussions regarding self-confidence. Data measurement was carried out using SPSS with independent sample t-test statistical analysis to determine the situation before and after the intervention was given. Based on the t-test value, it was found that the application of AMT data had a significant positive effect on increasing students' self-confidence as seen from the results of the equal variances assumed sig.2-tailed value <0.05.